Sports Development in North Lombok Regency Review from the Sports Development Index (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
Several aspects must support the progress of development. Likewise, in sports development, sports development should prescribe several aspects of dimensions, namely Human Resources, Participation, Prejudice, and Open Space. This study aims to (1) Analyze the availability of open space, (2) Analyze human resources, (3) Analyze community participation, (4) Analyze public fitness in North Lombok Regency. This research is a quantitative descriptive study, with a sample of 270 people, 90 each from 3 districts. The sampling technique uses a stratified random sampling technique with cluster sampling. Data collection instruments were carried out by observation, questionnaire, interview, documentation, MFT test. Data analysis techniques using interactive. Research results: (1) Open Space index value = 0.205, (2) Community Participation index value = 0.240, (3) Fitness index value = 0.395, (4) and Human Resource index value = 0.0006, (5) Results from the combination of the four-dimensional indexes it can be seen that the Sports Development in North Lombok Regency in terms of the sports development index is 0.209. This value, when viewed from SDI norms, is categorized as low. To increase the SDI index in the future, the Regional Government, Bappeda, Dikpora, KONI of North Lombok Regency, together with the community, must work extra hard to improve all components in a consultative manner, with priority at the low dimensions. Systematic and strategic efforts must be made to raise the sports development index going forward. An increase in the index means an improvement in the quality of sports development, as well as the community.